Entrepreneur Behavior of Brolier Farmers in Banyumas - Wakhidati, Yusmi Nur; Sugiarto, Mochamad; Aunurrohman, Hudri (ANIMAL PRODUCTION, 2019)
Entrepreneurial behavior is a series of actions of business actors to freely combine innovative resources to identify and pursue opportunities. This behavior is influenced by self-efficacy, perceptions of supporting contexts and ability to control attitudes. This study aims to identify the extent of and contributing factors to entrepreneurial behavior of broiler farmers in Banyumas. The data were collected from a survey engaging 60 farmers-members of partnership farming. The data were analyzed using descriptive statistical and correlation analysis. The results showed that the entrepreneurial behavior of farmers was in high category with an average score of 65.45. Farmers have a high category of self-efficacy with an average score of 18.55. Farmers' perceptions of supporting contexts and the ability of farmers to control attitudes are in the medium category with an average of 30.04 and 33.70 respectively. There was a significant relationship between entrepreneurial behavior and self-confidence and perceptions of supporting context, but no significant relationship with the ability to control attitudes. The relationship between entrepreneurial behavior and farmer self-confidence is in the weak category, while the relationship between entrepreneurial behavior and farmers' perceptions of supporting contexts is in the moderate category.